2004
DOI: 10.1063/1.1784931
|View full text |Cite
|
Sign up to set email alerts
|

Viscous fingering as a paradigm of interfacial pattern formation: Recent results and new challenges

Abstract: We review recent results on dynamical aspects of viscous fingering. The Saffman-Taylor instability is studied beyond linear stability analysis by means of a weakly nonlinear analysis and the exact determination of the subcritical branch. A series of contributions pursuing the idea of a dynamical solvability scenario associated to surface tension in analogy with the traditional selection theory is put in perspective and discussed in the light of the asymptotic theory of Tanveer and co-workers. The inherently dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(64 citation statements)
references
References 73 publications
1
62
0
1
Order By: Relevance
“…The steady finger shapes found by McLean & Saffman are linearly stable for modest B and are thought to be linearly stable whenever the surface tension is non-zero (Kessler & Levine 1986;Tanveer 1987;Casademunt 2004). However, for noisy systems with small B, the interface is unstable to tip-splitting behaviour both experimentally (Park & Homsy 1985;Maxworthy 1987;Tabeling, Zocchi & Libchaber 1987) and numerically (Casademunt 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The steady finger shapes found by McLean & Saffman are linearly stable for modest B and are thought to be linearly stable whenever the surface tension is non-zero (Kessler & Levine 1986;Tanveer 1987;Casademunt 2004). However, for noisy systems with small B, the interface is unstable to tip-splitting behaviour both experimentally (Park & Homsy 1985;Maxworthy 1987;Tabeling, Zocchi & Libchaber 1987) and numerically (Casademunt 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The instability of the double-fingered state with respect to asymmetric perturbations is consistent with the absence of states with two long Multiple finger propagation modes in Hele-Shaw channels of variable depth 141 fingers from experimental data for the rigid channel. We note that tip splitting and competition between fingers is a classic feature of experimental observations of fingering in Hele-Shaw cells at low surface tension (Park & Homsy 1985;Maxworthy 1987;Tabeling et al 1987) and in numerical investigations of evolution towards a single finger (Casademunt 2004). For these low-surface-tension cases, the tip-splitting behaviour is essentially triggered by experimental perturbations or numerical noise.…”
Section: Tip Splittingmentioning
confidence: 99%
See 1 more Smart Citation
“…Viscous fingering is one example of spontaneous pattern formation in far-from-equilibrium systems. Fingering patterns are seen in moving interfaces as the result of the growth of morphological fluctuations [12,13,14,15]. Stripe patterns are thus spontaneously generated when a thin film of viscous fluid is produced by passing it through a small gap [16,17,18,19,20] or when two pieces of adhesive tapes that are stuck together are peeled [21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Since the governing equations for the gap-averaged velocity are similar to Darcy's law, the Hele-Shaw cell also serves as a 2D model for flow through porous media, where the flow is governed by Darcy's law. The investigation of interface formation in immiscible flows with and without surface tension effects has revealed that this can be used as a generic model problem for analytical studies as well as for benchmarking numerical simulations of free surfaces [7,14,48,25,30] In our simulations we considered the flow in the narrow gap between the plates and investigated the finger by assuming that the tip can be fitted by an exponential shape as described in [30]. We used a channel [0, 32] × [−1, 1] with aspect ratio 16:1 using 16N grid points in x-direction, and N in y-direction.…”
Section: Viscous Fingeringmentioning
confidence: 99%